Double Contour Thermodynamic Cycle with Unidirectional Heat Transfer between the Refrigeration and the Energy Cycle - Gorpinko Yu.I.; Senetskyi O.V.; Sarapin V.P.; Shubenko O.L.; Malyarenko V.A.2 (Problems of the Regional Energetics)
Practical characteristics of the method for improving cycles of complex cooling thermotrans-formers associated with the regeneration of the refrigeration cycle heat productivity (RCHP) are considered. The use of heat from the working fluid compression in the reverse (refrigeration) cycle for heating the working fluid of the direct (energy) cycle has the theoretical advantages of opportunity to achieve the characteristics of the Carnot-Carnot thermotransformers. Aim of the research was to develop an effective cycle for a room cooler with a RCHP. The aim is achieved by developing a combined cycle with a minimum number of contours and researches of opera-tion mode changes of the regenerative heat exchanger (RHE). The most important results are the determination of the area of advantages of a heat activated cooler with RCHP over traditional builders heat activated cooler, which corresponds to the possibility of utilizing waste heat with a potential of 130 – 170 ºС, definition reserves for improving the characteristics of a cooler with RCHP, identifying significant quantitative and qualitative changes in the ratio of thermal equiva-lents of RHE, their correlations with cooler thermodynamic efficiency levels according. The sig-nificance of the obtained results is that when improving of the complex thermotransformers of cooling, minimizing the consumption of mechanical power by a reverse cycle is not always jus-tified; to achieve a high thermodynamic efficiency of a heat activated cooler with a RCHP, the most favorable modes of operation of its RHE with an approximate balance of thermal equiva-lents of flows.